LEGAL CONSEQUENCES OF USING SIJUKKOT PLANTS AS TRADITIONAL MEDICINE TO TREAT VARIOUS DISEASES USED BY THE SABULAN VILLAGE COMMUNITY AS TRADITIONAL KNOWLEDGE - Pandiangan, Tawarika M (DE'RECHTSSTAAT, 2024)
Sijukkot plant (in Latin: Lactuca Indica L) is a plant that is believed to have many properties in curing various diseases. This plant is not widely known, both from the name, morphology to the content of its properties that are beneficial for health. The phenomenon that occurred in Sabulan Village is that the people of Sabulan Village also do not know the existence of the importance of protecting traditional knowledge owned by the community is part of the protection of Intellectual Property Rights. Qualitative research methods with a descriptive approach through observation and interviews were carried out for this study with thematic data analysis techniques. This study aims to determine how the community processes the sijukkot plant into traditional medicine that is beneficial for health and how the community's knowledge and understanding of traditional knowledge that has been used is part of Intellectual Property Rights. The results show that many people do not know from the aspects of the name of the plant, the morphology of the sijukkot plant to its properties, so that the impact that occurs is that the community cuts down or throws away this plant to utilize the original area of ​​the plant into a place that according to the Village community is more profitable. It is very unfortunate, if the community has the knowledge plus is supported by the government to process the plant into a traditional medicine that is beneficial and has economic value, it will greatly help the welfare of the Village community.